DEVELOPMENT OF ANCIENT STYLE MUSIC COMMUNICATION IN THE NEW MEDIA ERA FROM MIMAN CULTURE MEDIA: DEVELOPMENT OF ANCIENT STYLE MUSIC COMMUNICATION IN THE NEW MEDIA ERA FROM MIMAN CULTURE MEDIA - Chen Yao; Ahmad Hisham Bin Zainal Abidin; Syamsul Hirdi Muhid (Jurnal Gendang Alam (GA), 2024)
ABSTRACT Miman Culture Media is the first cultural company in China that focuses on the promotion of original ancient style music, and has developed a large number of young group fans of traditional Chinese music and culture. In every stage of the company’s development, it reflects the market development trend of Chinese folk music in the era of new media, media dissemination channels, and changes in the connotation of traditional music. Combined with the development of Miman Culture Media, this paper adopts empirical methods such as interviews, online ethnography and participant observation to analyze the transmutation of ancient style music in Chinese pop music field in the era of new media from three aspects: cultural self-consciousness, market integration, and marketing of ancient style music, and to get the characteristics of the pluralism and cultural nature of Chinese ancientry music in the era of new media. Keywords: Miman Culture Media, ancient style music, new media, communication